FINDING THE PERFECT MATCH. - Barkin, Robert (American City & County, 2013)
This article discusses the popularity of cloud services among larger cities and counties as well as many smaller communities in the U.S. in 2013. The commonly cited benefits of the cloud technology was availability of service across multiple devices and cost savings. The article also describes the use of cloud services in disaster management.